#TITLE_ALTERNATIVE# - Lingga (NIM 235 05 006), Indra
Abstract: Airplane is designed through several phase. One of the phase is called conceptual design. Conceptual design itself is divided into several process, the first process of conceptual design is preliminary sizing. Preliminary sizing is a process to determine several airplane initial characteristics such as take off weight and wing size. A lot of calculation is involved in preliminary sizing process to ensure that the airplane which is designed meet several performace requirement and regulation. Because of that reason, optimization is involved in preliminary sizing process. There are several optimization criteria which is need to be determined when solving optimization problems. Preliminary sizing is categorized as non linear, multi variable, constrained dan multi objective problem. One of the optimization methods which can solve that kind of problem is TOPS method. TOPS is an optimization method which is composed from Trade Off, Interior Penalty, and Simplex method. The optimization of preliminary sizing involves a lot of calculation and iteration which can be time consumed if it is done manually. This thesiss main objective is to build a tool to help a designer do preliminary sizing process so the initial airplane design can be achieved faster. The tools is called PrelimSizing. PrelimSizing built through Object Oriented Software Engineering(OOSE) using Rational Unified Process (RUP).